PENURUNAN KADAR ION LOGAM KROMIUM PADA LIMBAH INDUSTRI SARUNG SAMARINDA DENGAN MENGGUNAKAN METODE ELEKTROKOAGULASI - Yulianti Kartika; Aman Sentosa Panggabean; Rahmat Gunawan (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2015)
The reduction of chromium concentration in Samarinda sarong wastewater by electrocoagulation method has been carried out. The research used Atomic Absorption Spectrophotometer (AAS) as an instrument determination level. To determination the optimum levels of each parameters by large percent qualified of electrocoagulation process with used variation of series parameters such as time contact, variation voltage and the distance of electrode. The result of research showed that degradation and is big of elimination percent of metal of Cr have an in with the effect of time contact, voltage and also distance of electrode at optimum hence in getting result of final concentration successively 31,250; 21,325 and 17,925 ppm of concentration early 50,650 ppm. Big of elimination percent of exclusion at optimum parameter in getting result successively 38,302; 57,897 and 64,610 %. Resulted in this research obtained optimum time contact is 30 minutes, optimum voltage is 4,5 volt and optimum distance of electrode is 1 cm.Keywords: Chromium, Samarinda sarong wastewater, Electrocoagulation, Metal electrode